Students' Writing Augmentation through Vocabulary, Connective, Opener, and Punctuation (VCOP) Strategy - Zahratul Idami; Dessy Kurniasy; Zaiyana Putri; Muhammad Rizky (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
This study was grounded in the observation that students often encounter challenges when attempting to initiate the introductory paragraph of a descriptive text due to insufficient command of vocabulary. Hence, this experimental research employed the VCOP strategy as a viable approach with the purpose was to enhance students' vocabulary, thereby influencing their writing skills. The research was conducted at SMK Negeri 5 Langsa, with X3 assigned as the experimental class and X5 as the control class. Each class comprised 32 students. The instruments employed in this study were pre-test and post-test. The findings indicated that the implementation of the VCOP was successful in enhancing students' writing proficiency. The statistical finding showed that the post-test score of the Experimental Group (EG) was greater than those of the Control Group (CG). The discrepancy between 69.38 and 57.19 was calculated to be 12.19. This disparity suggested that the administered treatment had a positive impact on pupils' learning outcomes. Furthermore, the t-test value of -3.8 obtained in this study exceeded the predetermined threshold, indicating a significant difference between the two groups. Consequently, the alternative hypothesis was accepted whereas the null hypothesis was rejected. The findings suggest that the academic performance of the experimental group was superior to that of the control group. Hence, VCOP is believed as an alternative strategy to be applied in writing classroom.